2021
DOI: 10.21203/rs.3.rs-156717/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Literacy, Information Seeking Patterns and Perceived Outcomes among Pregnant Women in Two Districts of Tanzania

Abstract: BackgroundPregnant women that engage in information seeking process are more likely to have a high level of knowledge about their health, be confident to discuss their health concerns with their health care providers and report better health promotion activities than individuals who do not seek health information. However, health literacy influence pregnant women’s information seeking behaviours and consequently their health knowledge and health outcomes. Limited studies have explored the effects of health lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…By contrast, inadequate levels of health information literacy have been associated with poor health decision-making (Heijmans et al, 2015), inadequate self-care and a lack of preventive behaviours (Soltani and Dickinson, 2005), and increasing rates of both hospitalization and mortality among women (Mahdizadeh and Solhi, 2018). Studies have also shown that women with inadequate levels of health information literacy are more likely to seek and access health information from non-credible sources, thus endangering their health (Kassim and Katunzi-Mollel, 2017; Mbekenga et al, 2021). This inadequacy is a barrier to women’s access to relevant health information that would help them make appropriate health decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, inadequate levels of health information literacy have been associated with poor health decision-making (Heijmans et al, 2015), inadequate self-care and a lack of preventive behaviours (Soltani and Dickinson, 2005), and increasing rates of both hospitalization and mortality among women (Mahdizadeh and Solhi, 2018). Studies have also shown that women with inadequate levels of health information literacy are more likely to seek and access health information from non-credible sources, thus endangering their health (Kassim and Katunzi-Mollel, 2017; Mbekenga et al, 2021). This inadequacy is a barrier to women’s access to relevant health information that would help them make appropriate health decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Socio-demographic factors such as education, income, marital status and age have been reported by numerous studies as determinant factors of health information literacy. Many studies, for instance, have associated higher levels of health information literacy with higher levels of education (Dumenci et al, 2014; Eriksson-Backa et al, 2012; McKee et al, 2015; Mbekenga et al, 2021; Sahm et al, 2012). In contrast, only a few studies have found no association between educational attainment and levels of health information literacy (see Muhanga and Malungo, 2018), thus suggesting that while education can be considered an important factor for health information literacy, in some contexts it is not.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pregnant women with stable incomes and occupations tend to have wider access to resources and can better comprehend health information. The literature reviewed revealed that most studies conducted in Tanzania on maternal health information have little documentation on pregnant women's comprehension of maternal health information ([ [7] , [8] , [9] , 15 ]). In fact, none of the studies has researched the influence of socio-demographic characteristics on pregnant women's understanding of maternal health information, particularly in the Coastal region.…”
Section: Introductionmentioning
confidence: 99%